Współczesne badania naukowe i postęp techniczny - Oryl, Kazimierz (Wydział Prawa i Administracji UAM, 1973)
As a result of the present-day technological-scientific revolution, technological advances became the main factor of economic growth. However, today technological advances demand a wide front of researches carried out directly in production. It is on this ground that science develops today very quickly and in a close connection with production. This union is a result of a long and complex process of change in research. In highly developed countries, those changes, which had begun already in the nineteenth century, took place in three principal directions. The first one consists in changes in the organization of science, the second in a process of a mathematical orientation of sciences and the third in the industrialization of researches. In Poland the employment of science in securing modern advances in technology was initiated as late as in the later sixties. That became necessary as a result of a shift towards a strategy of intensive growth. This, in turn demanded speeding up the development of science and closer ties between research and production. A number of reasons, and, above all, an economic underdevelopment and a comparatively short period of time available for bringing into effect the policy of intensive growth, contributed to the fact that in Polish science a complete change towards the above mentioned directions has not yet taken place. That is why science in Poland at the present moment is unable to perform its tasks assigned by production to such a degree as it is the case in highly developed countries.
Present day Scientific Research and Technological Advances